Antimony doped Si Esaki diodes without post growth annealing - Oehme, Michael; Kirfel, O.; Werner, J.; Kaschel, M.; Kasper, E.; Schulze, J. (Thin Solid Films, 2010)
Room temperature current density versus voltage characteristics of silicon Esaki diodes grown with molecular beam epitaxy are presented. The diodes are doped with boron and antimony. The integrated devices are realized without a post growth annealing step. Good peak to valley current ratios in excess of 3 and excellent peak current densities up to 5.2 kA/cm2 were found at room temperature. We present a detailed investigation of the influence on the boron surface segregation effects of the peak current density. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Esaki diodes; Molecular beam epitaxy; Silicon; Surface segregation